Pengaruh Siklus Panas pada Komposit Limbah Plastik HDPE-Serat Cantula sebagai Bahan Material Alternatif Melalui Uji Mekanik - Sunaryo; Burhan Ibnu Mubtadi (Politeknosains, 2016)
This research is to determine the effect of thermal cycling on mechanical properties of such composites. Mechanical properties test in the tensile strength, bending strength and impact strength. Composite materials using HDPE powder as a cosmetic bottle waste cantula matrix and fibers as reinforcement, fiber volume fraction is 40% composed of random. Specimens were made using a hot molding machine. Temperature thermal cycle with a variation of 60 ° C, 70 ° C, 80 ° C, 90 ° C and 100 ° C. Variations in the number of cycles performed 100 times. Testing of mechanical properties of the composite tensile strength using ASTM standard 3039, bending strength ASTM D 6272 standard, and impact strength testing with ASTM D 5941. Results of testing the mechanical properties of composites obtained the data that the composite thermal cycle with a temperature of 60 ° C were carried out as many as 100 times. The tensile strength of 26 MPa, bending strength of 29 MPa and impact strength 45 kJ / m². Composites with a thermal treatment at temperatures above 70 ° C resulted in the degradation of the material so that the mechanical strength decreases.